2005
DOI: 10.1521/suli.2005.35.4.388
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder and Deliberate Self‐Harm: Does Experiential Avoidance Play a Role?

Abstract: The theory that borderline personality disorder (BPD) is associated with experiential avoidance, and that experiential avoidance mediates the association between BPD and deliberate, nonsuicidal self-harm was examined. Female inmate participants (N = 105) were given structured diagnostic assessments of BPD, as well as several measures of experiential avoidance. There was a high lifetime prevalence of past self-harm (47.6%). Higher dimensional scores representing BPD severity were associated with higher self-har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 46 publications
(49 reference statements)
5
114
1
2
Order By: Relevance
“…An increase in expressive suppression interferes with the beneficial effects that cognitive reappraisal has on NSSI. This finding supports previous research showing that the use of escape and avoidance emotion regulation strategies, specifically expressive suppression, is associated with a higher frequency of NSSI in individuals with BPD (Chapman et al, 2005); but it also goes a step further by showing that expressive suppression interferes with the ability to reinterpret the meaning of a situation that elicits an undesired emotion. The second interaction shows that an increase in dissociation is to some degree related to an increase in NSSI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…An increase in expressive suppression interferes with the beneficial effects that cognitive reappraisal has on NSSI. This finding supports previous research showing that the use of escape and avoidance emotion regulation strategies, specifically expressive suppression, is associated with a higher frequency of NSSI in individuals with BPD (Chapman et al, 2005); but it also goes a step further by showing that expressive suppression interferes with the ability to reinterpret the meaning of a situation that elicits an undesired emotion. The second interaction shows that an increase in dissociation is to some degree related to an increase in NSSI.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with BPD research suggests that NSSI may be considered a maladaptive coping strategy (Welch, Linehan, Sylvers, Chittams, & Rizvi, 2008). In a research study the tendency to suppress unpleasant thoughts and/or emotions has been associated with a higher use of NSSI among incarcerated women with BPD but not among non-BPD individuals (Chapman et al, 2005). Moreover, in two other studies results showed that NSSI is seen as a means of providing relief from undesired thoughts and/or emotions (Chapman, Gratz, & Brown, 2006) or to escape from or avoid undesired emotions, situations, or aversive tension (Kleindienst et al, 2008) among BPD population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, strategies that do not process and use the information in a helpful way, perhaps rejecting or blocking emotions instead, would be considered dysfunctional. These strategies prevent the development of tolerance to emotions (Chapman, Specht, & Celluci, 2005) and may actually lead to amplification of emotional distress due to the generation of secondary emotions, such as feeling anxious about the initial 'bad' feelings (e.g., Linehan, 1993) or through the 'coupling' of emotions (e.g., Power & Dalgleish, 1997).…”
Section: A New Measure Of Emotion Regulation In Adolescentsmentioning
confidence: 99%
“…Support has emerged for models in which thought suppression mediates the relation between negative emotionality or emotional reactivity and suicidal ideation. [14,15] Chapman et al [16] similarly found that thought suppression was associated with a greater frequency of self-harm in a sample of female inmates with borderline personality disorder. Hence, converging evidence suggests that suppression of unwanted thoughts may be associated with greater suicidal ideation and potential for self-harm.…”
Section: Introductionmentioning
confidence: 97%